Endometrial and cervical osseous metaplasia with extramedullary haematopoiesis presenting as amenorrhea: Report of three cases - Iffat Jamal; Rakesh K Gupta; Surabhi Raj; Punam P Bhadani (Indian Journal of Pathology and Microbiology, 2020)
Endometrial and cervical osseous metaplasia (OM) is a rare phenomenon seen mostly in reproductive age group. Patients generally present with complaints of secondary infertility. Although few cases of endometrial OM have been described in literature, to the best of our knowledge, only six cases of OM in cervix have been reported so far. We report three cases of endometrial OM with extramedullary hematopoiesis, presented with complaints of amenorrhea and secondary infertility. In addition, one of the patients also had cervical OM.